2014
DOI: 10.1074/jbc.m114.568212
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue Modulates β-Secretase, Reverses Cerebral Amyloidosis, and Improves Cognition in Transgenic Mice

Abstract: Amyloid precursor protein (APP) proteolysis is required for production of amyloid-β (Aβ) peptides that comprise β-amyloid plaques in the brains of patients with Alzheimer disease (AD). Here, we tested whether the experimental agent methylene blue (MB), used for treatment of methemoglobinemia, might improve AD-like pathology and behavioral deficits. We orally administered MB to the aged transgenic PSAPP mouse model of cerebral amyloidosis and evaluated cognitive function and cerebral amyloid pathology. Beginnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 84 publications
6
39
0
Order By: Relevance
“…Alzhemed was stopped after human trials and Methylene Blue variants [13 ] are undergoing human trials. 2 with one N-methylated residue, inhibits Ab aggregation and toxicity.…”
Section: Alzhemed and Rembermentioning
confidence: 99%
“…Alzhemed was stopped after human trials and Methylene Blue variants [13 ] are undergoing human trials. 2 with one N-methylated residue, inhibits Ab aggregation and toxicity.…”
Section: Alzhemed and Rembermentioning
confidence: 99%
“…Callaway et al [125] showed that the assistance provided by MB during oxidative phosphorylation was able to improve memory retention in rats. MB has also been shown to prevent oligomerization of A␤ as well as its extracellular accumulation forcing aggregates to go through nucleate fibril formation [126,127]. This is done by targeting beta secretase-1 (BACE1) reducing its stability and reduces ␤-secretase activity which decreases the number of A␤ species [127].…”
Section: Methylene Bluementioning
confidence: 99%
“…28 MB also reduced soluble Aβ and rescued early cognitive deficit in AD transgenic mice. 29 In HD, MB can slow down the aggregation of mHTT protein even when aggregation has already been initiated, and aggregated species were presented in vitro . 8 In primary neurons expressing mHTT, MB reduced the formation of both oligomeric and insoluble mHTT and increased the survival of neurons.…”
Section: Discussionmentioning
confidence: 99%